Eigensolutions and thermodynamic properties of generalized hyperbolic Hulthen and Woods-Saxon potential - Y. M. Assimiou; S. T. Daniel; G. Issoufou; D. F. Anselme; G. Y. H. Avossevou (Condensed Matter Physics, 2024)
In this paper, we present the solutions of the Schrödinger equation and the thermodynamic properties of generalized hyperbolic Hulthen and Woods-Saxon potential. The eigenvalues and eigenfunctions were found using the parametric Nikiforov-Uvarov method (PNUM). The clean energies of the molecules HCl, NiC, CO, I2, H2, LiH, CuLi and CrH are calculated for certain values of n and l. They are positive and close to the energy of the ground state (n = l = 0) in the case of the atomic unit (whose energies become negative for n = 2). The figures show that the proper energies decrease as n, l, α increase, while they increase as m increases, which confirms the results obtained in the literature. The obtained energy was used to calculate the partition function from which thermodynamic properties such as average energy, specific heat capacity, entropy and free energy are calculated. Numerical results are generated for this generalized hyperbolic Hulthen and Woods-Saxon potential. This study showed that the disorder dec reases if the temperature decreases and this decrease is more rapid for HCl and H2 molecules.